Study of Cherry Stones as a Precursor in the Preparation of Low Cost Carbonaceous Adsorbent - Beker, U.; Dertli, H.; Duranoglu-Gulbayir, D.; Cakan, R. D. (TAYLOR & FRANCIS INC, 2010)
A cherry stone-based activated carbon was electrochemically and chemically oxidized to enhance its adsorbent property for comparison with as-produced. The samples obtained were characterized by Boehm's titration, pH titration, zeta potential measurement, FT-IR, Brunauer-Emmet-Teller surface area, and pore size distribution. A significant increase in the concentration of surface functional groups was obtained from the oxidation of the samples due to the introduction of oxygen-containing functional groups, as confirmed by Boehm's titration, FT-IR, PZC, and IEP analyses. Activation methods significantly improved the amount of oxygen-containing surface functional groups that make the carbonaceous adsorbents more hydrophilic and acidic, decreasing the pH of their point of zero charge, and increasing their surface charge density. The activated carbon samples obtained were predominantly microporous, and their pore volumes decreased as a function of activation period and temperature. The surface chemistry development of carbons was correlated to increasing removal ability of heavy metals.
Keywords: activated carbon; carbonization; cherry stone; lignocellulosic waste; oxidation; ACTIVATED CARBONS; ELECTROCHEMICAL OXIDATION; SURFACE-CHEMISTRY; SORPTION; SPECTROSCOPY; FIBERS; OXIDES; IONS; Energy & Fuels; Engineering; Environmental Sciences & Ecology